(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2025)
This study aims to investigate teachers’ conceptions regarding the topic of meiosis, with the goal of contributing to the field of science education research by providing insights that support the understanding and overcoming of difficulties related to the appropriation of genetic knowledge. Additionally, it seeks to address a gap in the literature on genetics education, particularly the lack of studies focused on in-service teachers. For data collection, the Meiosis Concept Inventory (MCI) was used—a tool previously developed and validated by American researchers. Our research group adapted and employed the MCI for the first time in Brazil, with the purpose of identifying alternative conceptions held by both students and teachers. The conceptions of 318 in-service teachers were analyzed. The results include a comparative analysis with undergraduate students in Biological Sciences, based on data from a previous study that used the same instrument. Overall, the in-service teachers performed worse than the undergraduates, although both groups exhibited a significant prevalence of alternative conceptions concerning basic genetic concepts related to meiosis. These findings reveal a limited understanding of this biological process among participants, which poses a challenge for effectively teaching this topic in basic education and highlights a critical area of concern for teacher training programs.